14 UPM postgraduate students participated in the DNA lecture, broaden students' understanding of DNA - Abdull Manap, Mohd Rashidi (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2023)
PETALING JAYA, 26 June - 14 postgraduate students from the Department of Chemistry, Faculty of Science, Universiti Putra Malaysia (UPM) attended a lecture by renowned deoxyribonucleic acid (DNA) scientist Nor Aidora Saedon which took place at the Department of Chemistry Malaysia to broaden students' understanding of deoxyribonucleic acid (DNA) forensics and its importance in criminal investigations, recently.